VARIETY OF DRUGS SOLD WITHOUT PRESCRIPTION FOR COMMONLY PRESENTING COMPLAINTS IN RURAL AND URBAN PHARMACIES OF FAISALABAD DISTRICT - Muhammad Hamza Rana; Muhammad Husnain; Muhammad Hamza Iqbal; Noor-i-Kiran Naeem; Usman, Muhammad; Yaqoob, Yasir (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Pharmacies play an important role in provision of health care to the community.The objective of the study was to explore the reasons for a variety of drugs sold without prescription for commonly presenting complaints in Rural and Urban Pharmacies of Faisalabad District. METHODOLOGY: This explanatory sequential mixed method design involved workers from twenty-five pharmacies from urban and rural areas of Faisalabad from February to July 2020. After obtaining informed consent, fifty pharmacy workers filled a pre-designed questionnaire (followed by twenty-five semi-structured, individual, face-to-face interviews. Quantitative data was analyzed via SPSS software and transcribed interviews were organized manually for data analysis. RESULTS: Response rate was 76.2%. As reported by the pharmacists,40% and 90% of urban and rural population respectively came to pharmacies for over-the-counter drugs. Fifty percent belonged to middle class among urban and 70% belonged to rural population. Data analysis led to formation of 36 codes, 6 subthemes and 3 themes. Out of the four reasons quoted by the pharmacists (time constraints, lack of basic facility locally, financial constraints, and myths/fear of going to doctor), there was a statistically significant difference for rural population going directly to pharmacies because of financial constraints. CONCLUSION: Lack of education and financial constraints are the leading influential factors for people taking over-the-counter drugs in both rural and urban population, with time constraints being at the top list among urban population. Robust policies and public health care programs can lead to public awareness at large and can help in creating an environment of health care provision with MINIMAL RISKS.